TNF receptor p55 controls early acute graft-versus-host disease. - Speiser, D; Bachmann, M; Frick, T; McKall-Faienza, K; Griffiths, E; Pfeffer, K; Mak, T; Ohashi, P (1997)
Allogeneic bone marrow transplantation is frequently associated with graft-vs-host disease (GVHD). To understand the effector mechanisms of GVHD, we investigated the role of the TNF receptor p55 (TNFRp55), which is known to be important in inflammation and cytotoxicity. After the transplantation of allogeneic bone marrow and spleen cells to lethally irradiated mice, all wild-type recipients developed early lethal GVHD within 1 wk, whereas TNFRp55-deficient recipients had much reduced GVHD and survived for at least 3 wk. No defect in alloantigen presentation was found, since T cell proliferation and cytotoxicity were similar to allogeneic wild-type and TNFRp55-deficient stimulator and target cells. Also, TNF alpha release did not differ significantly between the two types of recipients. Therefore, early acute GVHD in wild-type mice was primarily due to TNFRp55-mediated tissue damage. Interestingly, lethal GVHD was not entirely dependent upon the TNFRp55. In experimental conditions using sublethal irradiation and high donor spleen cell numbers, TNFRp55-deficient recipient mice developed lethal GVHD with similar kinetics and frequency as the control mice. These data suggest that the effector mechanisms leading to organ damage in murine acute GVHD can be dissected in a cytokine pathway through the TNFRp55, as demonstrated here, and in a cellular pathway through direct interaction of cytotoxic lymphocytes with target tissues involving perforin and Fas/Fas ligand, as reported previously.